Factors Contributing to the Decline of the Anchovy Fisheries in Krueng Raya Bay, Aceh, Indonesia - Imran, Zulhamsyah; Yamao, Masahiro (Annals of Tropical Research, 2014)
Anchovy fisheries in Indonesia faces an imminent collapse in the next decade. This research explores some crucial factors contributing to the overfishing or depletion of anchovy resources. It was conducted in Krueng Raya Bay during September – October 2012. Survey, focus group discussion and interviews were implemented to explore the state of anchovy and coastal ecosystem degradation. It was shown that 52% of the total production was caught by lift net boats during the west monsoon season of 2012. Simple regression analysis resulted to different models of MSY either before or after the tsunami in 2004 which were shown as y = 0.8696 – 0.00008x and y=0.1138 – 0.00002x, respectively. Model 1 recommended reducing the number of lift net boat to 43 units for optimization of yield. On the other hand, Model 2 suggested that only 23 units could be operated for optimal effort each year. Average recent catch in MSY showed 53.9% (less abundant) before the tsunami and 5.5% (depletion) after that. These conditions was led by increasing effort, un-friendly, destructive fishing gears, and degradation of coral reef and mangrove. Such a tragedy was accelerated by anthropogenic factors and compounded by the tsunami factor. The tsunami impact on anchovy fishery depletion may be lesser than the combined effects of destructive fishing and anthropogenic factors.